2003
DOI: 10.1046/j.1365-2958.2003.03567.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of additional TnrA‐regulated genes of Bacillus subtilis associated with a TnrA box

Abstract: SummaryBacillus subtilis TnrA is a global regulator that responds to the availability of nitrogen sources and both activates and represses many genes during nitrogen-limited growth. In order to obtain a holistic view of the gene regulation depending on TnrA, we performed a genome-wide screening for TnrAregulated genes associated with a TnrA box. A combination of DNA microarray hybridization and a genome-wide search for TnrA boxes allowed us to find 36 TnrA-regulated transcription units associated with a putati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
133
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(136 citation statements)
references
References 28 publications
3
133
0
Order By: Relevance
“…To screen for additional LmrA targets, we employed a strategy analogous to that used in a previous study involving combined DNA microarray and gel retardation analyses (26). DNA microarray analysis was performed as described previously (26).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To screen for additional LmrA targets, we employed a strategy analogous to that used in a previous study involving combined DNA microarray and gel retardation analyses (26). DNA microarray analysis was performed as described previously (26).…”
Section: Methodsmentioning
confidence: 99%
“…To screen for additional LmrA targets, we employed a strategy analogous to that used in a previous study involving combined DNA microarray and gel retardation analyses (26). DNA microarray analysis was performed as described previously (26). B. subtilis strains PLR2 and 168 were grown in LB liquid medium, and then the cells were harvested in the middle of the logarithmic phase at an optical density at 600 nm of 0.5 and disrupted to extract total RNA by vigorous shaking with glass beads in the presence of sodium dodecyl sulfate and phenol (25).…”
Section: Methodsmentioning
confidence: 99%
“…29), its own gene (tnrA; see Ref. 23), and other genes of nitrogen assimilation (30). Moreover, TnrA acts as a repressor for the genes gltAB and glnRA (31) as well as some other genes (30).…”
mentioning
confidence: 99%
“…23), and other genes of nitrogen assimilation (30). Moreover, TnrA acts as a repressor for the genes gltAB and glnRA (31) as well as some other genes (30). Concerning the mechanism of control of TnrA activity, it could be shown that feedback-inhibited GS directly interacts with TnrA and blocks its DNA binding activity under conditions of good ammonium supply (32).…”
mentioning
confidence: 99%
“…It is known that expression of glutamine synthetase (GlnA) is necessary for function of the transcription factor TnrA, which is a global regulator of nitrogen metabolism genes (34). When bound to feedback inhibitors, GlnA binds to TnrA and prevents its DNA from binding to genes regulated by a TnrA box sequence (34,35). To determine if the surface growth effects seen with the glnA mutant were a result of disruption of controls of TnrA, we constructed a tnrA mutant strain (MH11) in the 3610 genetic background.…”
mentioning
confidence: 99%